Multifunctional injectable composite hydrogel loaded with active oxygen response polymer micelle as well as preparation method and application of multifunctional injectable composite hydrogel

By developing load active oxygen response to relieve polymer beam multifunctional injection of composite hydrogel, solve the problem of decreased Chinese drug concentration, systemic side effects and drug delivery systems in existing RA treatment The intelligent control of the drug and the effective removal of joint activation oxygen in the joints significantly improved the treatment effect of RA.

CN119367274APending Publication Date: 2025-01-28SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411532499.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing treatment methods for rheumatoid arthritis (RA) have problems with lower drug concentrations, systemic side effects, and the inability of drug delivery systems to accurately respond to the joint microenvironment, resulting in insufficient concentration of drugs in the lesion site and ineffective inhibition of inflammation and joint destruction.

Method used

Develop a load active oxygen response to the multi -function of polymer beam to inject composite hydraulic gel, generate bisodidalized hyaluronic acid through the reaction between sodium iodine and hyaluronic acid, and decorate the chitosaccharides with the dietic anhydride Combine with the active oxygen response polymer beam to form a stable hydrogel network and realize the intelligent control release of the drug.

Benefits of technology

This hydrogel can adjust the release rate of the drug according to the active oxygen level in the joint, accurately locate the inflammatory joints, reduce whole body side effects, effectively remove excessive active oxygen, reduce the inflammatory response, inhibit bone erosion, and promote cartilage repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367274A_ABST
    Figure CN119367274A_ABST
Patent Text Reader

Abstract

The invention discloses multifunctional injectable composite hydrogel loaded with active oxygen response polymeric micelles and a preparation method and application of the multifunctional injectable composite hydrogel, and belongs to the technical field of biomedical hydrogels, oxidized hyaluronic acid, modified chitosan and active oxygen sensitive micelles are fused in the hydrogel, and intelligent regulation and control over the rheumatoid arthritis microenvironment are achieved. Through a dual crosslinking technology, the hydrogel not only has improved mechanical strength, but also has shape adaptation and self-repairing capabilities. Due to introduction of the active oxygen response micelle, drug release is intelligent, the release rate is adjusted according to the level of active oxygen in joints, and the curative effect is enhanced; the hydrogel can accurately locate an inflamed joint, intelligently release drugs, reduce side effects, induce polarization of M2 macrophages, improve an inflammatory microenvironment and realize collaborative treatment, intelligent controlled release and long-term stability of the hydrogel provide a new strategy for precision medicine, and the hydrogel is expected to show huge potential in treatment of rheumatoid arthritis and has broad application prospects. Important clinical application values and market prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical hydrogels, and specifically relates to a multifunctional injectable composite hydrogel loaded with active oxygen responsive polymer micelles, and a preparation method and application thereof. Background Art

[0002] Rheumatoid arthritis (RA) is a prevalent autoimmune disease characterized by chronic synovitis, bone erosion, and joint destruction. The global prevalence of RA ranges from 0.24% to 1%, and cases are expected to increase by 80.2% by 2050. This escalating burden is associated with significant complications, disability, and mortality, adversely affecting patients' quality of life and productivity. The pathogenesis of RA is complex, mainly involving the degradation of articular cartilage and extracellular matrix, as well as the excessive production of intracellular reactive oxygen species (ROS). These adverse microenvironments further aggravate the infiltration of activated macrophages, leading to synovial inflammation and joint destruction.

[0003] At present, although there are various treatment methods for RA, there are still many challenges. Traditional therapeutic drugs such as methotrexate (MTX) have certain efficacy, but they are often affected by problems such as reduced drug concentration and systemic side effects. The existing drug delivery system cannot achieve accurate drug release according to changes in the joint microenvironment (such as pH value, ROS level, etc.), resulting in insufficient drug concentration in the lesion site, unable to effectively inhibit inflammation and joint destruction, and toxic effects in non-lesion sites. Although the application of nanotechnology and materials science in the medical field has become increasingly widespread in recent years, the drug delivery system based on responsive nanomaterial carriers cannot meet the needs of clinical treatment because the nanocarriers are easily cleared in the body due to size problems. In addition, the long-term safety and stability of nanocarriers also need further evaluation and research.

[0004] In summary, the current status of RA treatment still faces many challenges. Although the traditional methotrexate (MTX) treatment method is effective, it has problems such as reduced drug concentration and systemic side effects, which limit its therapeutic effect. Existing drug delivery systems are insufficient in responding to the joint microenvironment. They cannot dually respond to the slightly acidic environment and high ROS levels in joint inflammation, and cannot achieve long-term precise controlled release of drugs and removal of ROS. Therefore, it is particularly important to develop a new composite delivery system that can achieve dual-stage precise controlled release of drugs, reduce systemic side effects, effectively remove reactive oxygen species in joints, and promote cartilage repair. Summary of the invention

[0005] In view of the complex pathogenesis of RA, which involves the degradation of articular cartilage and extracellular matrix and the excessive production of ROS, the existing drug delivery systems for RA have deficiencies in precise controlled release, responsiveness, disease specificity, etc., and there is an urgent need to develop a drug delivery system that can simultaneously eradicate intracellular reactive oxygen species, regulate the joint microenvironment and promote cartilage repair. The present invention aims to provide a multifunctional injectable composite hydrogel loaded with reactive oxygen responsive polymer micelles, and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution: The present invention provides a method for preparing a multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles, comprising: S1, sodium periodate aqueous solution reacts with hyaluronic acid at room temperature, dialyzes, and dries to obtain dialdehyde hyaluronic acid; S2, chitosan is dissolved, reacted with an acid solution containing succinic anhydride, the precipitate is collected and dialyzed, and freeze-dried to obtain succinic anhydride-modified chitosan; S3, preparation of active oxygen responsive polymer micelles; S4, dialdehyded hyaluronic acid is dissolved in a solution containing polymer micelles and mixed with adipic acid dihydrazide solution of succinic anhydride-modified chitosan to obtain a multifunctional injectable composite hydrogel loaded with active oxygen-responsive degradation polymer micelles; The mass concentration of the dialdehyde hyaluronic acid solution is 3%~7%; the mass concentration of the succinic acid modified chitosan is 5wt%~7wt%, the mass concentration of the adipic acid dihydrazide solution is 5wt%~7wt%; the concentration of the active oxygen responsive polymer micelle is 5mg / mL In S1, the molar ratio of sodium periodate to hyaluronic acid is 1-2:1.

[0007] Furthermore, in S1, the dialysis uses a dialysis bag with a molecular weight cutoff of 3500Da.

[0008] In S2, the molar ratio of chitosan to succinic anhydride is 1:1-3, and the reaction is carried out at 23°C-27°C for 11h-15h.

[0009] Furthermore, in S2, the solvent used to dissolve the chitosan is a mixed solvent of acetic acid and ethanol.

[0010] Furthermore, in S2, the pH value is adjusted to 9-10 before collecting the precipitate, and the molecular weight cutoff of the dialysis bag used for the dialysis is 10KDa.

[0011] In S3, the step of preparing active oxygen responsive polymer micelles comprises: S31, mixing 3-mercaptopropionic acid, acetone and trifluoroacetic acid, stirring at room temperature, ice bathing until crystallization is complete, filtering, washing, and drying to obtain ketal mercaptan; S32, stirring thioketal, N,N'-diisopropylcarbodiimide and 4-dimethylaminopyridine in dichloromethane, adding dropwise methoxy polyethylene glycol dissolved in dichloromethane, stirring under nitrogen atmosphere, precipitating with cold ether three times, filtering, dissolving the solid in water, and dialyzing to obtain methoxy polyethylene glycol-thioketal; S33, adding methoxy polyethylene glycol-ketalthioate to a dimethylsulfoxide aqueous solution containing N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, stirring at room temperature, adding ammonia disodium solution dropwise, stirring for reaction, dialyzing, and freeze-drying to obtain methoxy polyethylene glycol-ketalthioate-methyldisodium; S34, dissolving methoxypolyethylene glycol-thioketal-methylamine dissolves, ultrasonicates in a water bath, and assembles in water to obtain active oxygen responsive polymer micelles.

[0012] Furthermore, in S31, the mass ratio of the 3-mercaptopropionic acid, acetone and trifluoroacetic acid is 5-6:2-3:1.

[0013] Furthermore, in S32, the mass ratio of thioketal, N,N'-diisopropylcarbodiimide and 4-dimethylaminopyridine is 1~2:1:0.1~0.2.

[0014] Furthermore, in S33, the feed mass ratio of the methoxypolyethylene glycol-thioketal, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 6~7:0.6~0.7:0.7~0.9.

[0015] Further, in S34, the methoxypolyethylene glycol-thioketal-methylamine is dissolved in dimethyl sulfoxide at a concentration of 1 mg / mL~5 mg / mL, and the volume ratio of dimethyl sulfoxide to water is 1~2:1.

[0016] In S4, the volume ratio of the dialdehyde hyaluronic acid solution to the adipic acid dihydrazide solution of succinic anhydride modified chitosan is 1:1.

[0017] The invention provides a multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles obtained by the preparation method.

[0018] The multifunctional injectable composite hydrogel comprises dialdehyded hyaluronic acid, succinic anhydride modified chitosan and active oxygen responsive polymer micelles; the active oxygen responsive polymer micelles are triblock polymers coupled with the drug methotrexate, comprising a hydrophilic polymer segment, a hydrophobic polymer segment and an active oxygen sensitive thioketal segment located in the middle.

[0019] The present invention provides application of the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles in the preparation of injection medicaments for rheumatoid arthritis.

[0020] Compared with the prior art, the technical solution of the present invention has achieved the following beneficial technical effects: The present invention provides a method for preparing a multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles, which forms a double-crosslinked hydrogel network through a crosslinking reaction between dialdehyde hyaluronic acid and adipic acid dihydrazide, and an interaction between chitosan and hyaluronic acid, thereby not only improving the mechanical strength of the hydrogel, but also giving it shape adaptability and self-repairing ability; the introduction of active oxygen responsive polymer micelles realizes intelligent controlled release of drugs, and can adjust the release rate of drugs according to the active oxygen level in the joints, thereby improving the therapeutic effect.

[0021] Furthermore, through the reaction of sodium periodate and hyaluronic acid, hyaluronic acid is converted into dialdehyde hyaluronic acid (OHA), which increases the cross-linking ability of hyaluronic acid and enables it to form a more stable hydrogel network with other components. At the same time, the dialdehyde group provides active sites for subsequent cross-linking reactions; through the modification of succinic anhydride, not only the solubility of chitosan is improved, but also carboxyl groups are introduced, enhancing its interaction with other components, thereby improving the stability and biological activity of the hydrogel.

[0022] Furthermore, a thioketal with active oxygen sensitivity was synthesized through the reaction of 3-mercaptopropionic acid with acetone and trifluoroacetic acid. The thioketal can break in the presence of active oxygen, thereby triggering the release of the drug; the thioketal was combined with methoxypolyethylene glycol and then coupled with the drug methotrexate to form a triblock polymer. The polymer is both hydrophilic and hydrophobic, and can self-assemble into nano-micelles in water, while carrying drugs and responding to the stimulation of active oxygen; the prepared MPEG-TK-MTX micelles were introduced into the hydrogel, so that it can respond to the level of active oxygen in the joint and intelligently release the drug, which not only achieves the controlled release of the drug, but also improves the targeting and bioavailability of the drug.

[0023] The multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles provided by the present invention is a new dual intelligent sustained-release multifunctional injectable composite hydrogel, which combines oxidized hyaluronic acid, succinic anhydride modified chitosan and active oxygen responsive polymer micelles to achieve intelligent regulation of the inflammatory microenvironment of rheumatoid arthritis; by introducing active oxygen responsive polymer micelles, the hydrogel can intelligently respond to the active oxygen level in the joint and effectively remove excessive active oxygen, thereby alleviating inflammatory response, inhibiting bone erosion, and promoting cartilage growth; oxidized hyaluronic acid and chitosan are both natural polymer materials with good biocompatibility, and their degradation products in the body are also non-toxic, so the hydrogel has high safety when used in vivo; the hydrogel has shape adaptability and self-repairing ability, can effectively conform to the shape of irregular articular cartilage, and automatically repair when damaged, thereby maintaining its stability and therapeutic effect.

[0024] The application provided by the present invention is that the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradable polymer micelles can accurately locate the inflamed joint site and intelligently release drugs to achieve precise treatment and reduce the systemic side effects of drugs. By regulating the level of active oxygen in the joint, the hydrogel can induce M2 macrophage polarization, downregulate the expression of inflammatory factors, and improve the microenvironment of rheumatoid arthritis, ultimately achieving a synergistic treatment effect; the hydrogel has intelligent controlled release and long-term stability, it can continuously play a role in the joint, reduce the recurrence and progression of the disease, and thus improve the quality of life of patients; it provides potential strategies and methods for the treatment of new precision medicine, promotes the development and application of precision medicine in the treatment of chronic diseases such as rheumatoid arthritis, and has potential clinical application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The NMR spectrum of the active oxygen responsive polymer micelle PTM prepared in Example 1 of the present invention; Figure 2 This is the NMR spectrum of the dialdehyded hyaluronic acid (OHA) prepared in Example 1 of the present invention; Figure 3 This is the NMR spectrum of succinic anhydride modified chitosan (NSCS) prepared in Example 1 of the present invention; Figure 4 This is a dynamic light scattering curve of the active oxygen responsive polymer micelle PTM prepared in Example 1 of the present invention; Figure 5 This is a PTM scanning electron microscopy image of the active oxygen responsive polymer micelles prepared in Example 1 of the present invention; Figure 6 Rheological characterization of the composite injectable hydrogel prepared in Example 1 of the present invention; Figure 7The injectable characterization of the composite injectable hydrogel prepared in Example 1 of the present invention; Figure 8 Characterization of shape adaptability of the composite hydrogel prepared in Example 1 of the present invention; Fig. 9 The self-healing performance characterization of the composite injectable hydrogel prepared in Example 1 of the present invention; wherein A is a microscopic characterization and B is a macroscopic characterization; Fig.10 This is the swelling spectrum of the composite injectable hydrogel prepared in Example 1 of the present invention at pH=6.8 / 7.4; wherein A is the swelling characteristic and B is the degradation characteristic; Fig.11 This is the degradation profile of the composite injectable hydrogel prepared in Example 1 of the present invention at pH=6.8 / 7.4; wherein A is the swelling characteristic and B is the degradation characteristic; Fig.12 This is a drug release diagram of the composite injectable hydrogel prepared in Example 1 of the present invention; Fig.13 is the DPPH scavenging ability of the composite injectable hydrogel prepared in Example 1 of the present invention, wherein A is the change of absorbance of DPPH solutions of different concentrations with wavelength, and B is the scavenging effect of HC, PTM and HC@PTM solutions on DPPH under the same conditions; Fig.14 The in vitro anti-inflammatory ability of the composite hydrogel prepared in Example 1 of the present invention; wherein A is the peak area of ​​(Control, HC, PTM, HC@PTM), and B is the fluorescence intensity; Fig.15 This is a schematic diagram of the time after the composite hydrogel of the present invention is treated in vivo; Fig.16 The results of HE staining, safranin 0-fast green staining, toluidine blue staining and type II collagen immunohistochemical staining of tissue sections after treatment with the composite hydrogel of the present invention. DETAILED DESCRIPTION

[0026] The following examples are used to further illustrate the present invention, but these examples are only for better understanding of the invention and are not intended to limit the scope or implementation principles of the present invention. The implementation methods of the present invention are not limited to the following. Unless otherwise specified, the test methods used are conventional methods, and the raw materials used are commercially available products.

[0027] Example 1 This embodiment provides a multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles, and the specific preparation steps are as follows: (1) Preparation of reactive oxygen species-responsive polymer micelles PTM Step 1: A mixture of mercaptopropionic acid (11.44 g, 108.02 mmol), acetone (2.90 g, 49.1 mmol) and 2 mL of trifluoroacetic acid (TFA) was stirred at room temperature for 6 hours. The mixture was placed in an ice bath until crystallization was complete; then, the solution was filtered and washed with n-hexane and cold water; and keto acid thiol (TK) was obtained after drying in a vacuum oven overnight.

[0028] Step 2: Dissolve TK (2 g), N,N'-diisopropylcarbodiimide (DIC, 1.01 g), and 4-dimethylaminopyridine (DMAP, 0.138 g) prepared in the first step in dichloromethane (DCM, 25 mL) and stir at room temperature for 2 h to obtain a mixed solution; completely dissolve mPEG2000 (4 g, 2 mmol) in 5 mL DCM and add dropwise to the above mixed solution, and stir in a nitrogen atmosphere for 48 h; precipitate with cold ether three times, filter, and dissolve the obtained solid in water, and dialyze through a dialysis bag (MWCO, 3500 Da) for 72 h to obtain mPEG-TK.

[0029] Step 3: Dissolve the mPEG-TK (51.58 mg), NHS (4.8 mg), and EDC (5.28 mg) prepared in the second step in 10 mL of DMSO, stir under a nitrogen atmosphere to obtain a mixed solution; dissolve MTX (18 mg) in 5 mL of DMSO, add it dropwise to the above mixed solution, and stir at 45°C for 24 h; dialyze the solution with deionized water (MWCO, 3500Da) for 48 h, and freeze-dry to obtain mPEG-TK-MTX solid powder.

[0030] Step 4: The mPEG-TK-MTX prepared in step 3 was dissolved in a mixed solution (DMSO and water in a volume ratio of 1:1), and dialyzed in deionized water (MWCO, 3500Da) for 48 h to remove the organic solvent, thereby obtaining self-assembled active oxygen responsive polymer micelles. The NMR spectrum of the active oxygen responsive polymer micelles is shown in the attached Figure 1 shown.

[0031] By the attached Figure 1 (From top to bottom they are mPEG-TK-MTX, mPEG-TK, TK) data show that the attached Figure 1 In the figure, a is the characteristic peak of TK, which appears at 1.53 ppm; b is the spectrum of mPEG-TK. In addition, the characteristic peaks of methoxy polyethylene glycol appear at 3.58 ppm and 3.61 ppm, indicating that the grafting reaction of methoxy polyethylene glycol is successful; in the spectrum of mPEG-TK-MTX 1 In the HNMR spectrum, the proton peaks of MTX are 7.36 and 7.01 ppm, respectively, indicating that the coupling of MTX is successful. In summary, the successful preparation of triblock polymer micelles is demonstrated.

[0032] (2) Preparation of dialdehyde hyaluronic acid (OHA) Specifically, 2.00 g of hyaluronic acid was dissolved in 50 mL of distilled water, stirred at 600 r / min in a 37 ℃ water bath until completely dissolved, and then 1.30 g of sodium periodate was added after cooling to room temperature. After continuous stirring for 12 h in a 25 ℃ water bath, 1 mL of ethylene glycol was added to quench the unreacted sodium periodate, and stirring was continued for 1 h. The product was then placed in a dialysis bag (with a relative molecular weight cutoff of 3500), dialyzed with distilled water for 48 h, and then freeze-dried to obtain OHA. The NMR spectrum of the dialdehyde hyaluronic acid is shown in Figure 2 shown.

[0033] By the attached Figure 2 From the data, three small peaks were observed in the range of 4.9-5.3 ppm, indicating the presence of oxidized aldehyde groups. These findings verified the successful modification of OHA.

[0034] (3) Preparation of succinic anhydride modified chitosan (NSCS) Specifically, 1.5 g of CS (chitosan) was placed in a flask, and 150 mL of 5% (v / v) acetic acid was added to dissolve in 180 mL of ethanol solution. After sufficient stirring and dissolution, 60 mL of acetone solution containing 2.25 g of succinic anhydride was added dropwise to obtain a reaction solution, which was reacted in a water bath at 25°C for 13 h. After the reaction, the precipitate was collected and dispersed in an ethanol solution, and 5% (w / v) sodium hydroxide was added dropwise to adjust the pH to 9-10, and the precipitate was collected again. The obtained precipitate was dissolved in deionized water, and then the solution was placed in a dialysis bag (8kDa-14kDa), dialyzed with deionized water for 48 h, and freeze-dried to obtain NSCS, whose nuclear magnetic resonance spectrum is shown as follows: Figure 3 shown.

[0035] By the attached Figure 3 The data show that in NSCS 1 Two characteristic peaks at 2.45 ppm and 2.53 ppm appeared in the H NMR spectrum, confirming the successful coupling of succinic anhydride with the chitosan molecular chain through -NH(CO)CH2- and -CH2COO- bonds, respectively. These findings verified the successful modification of NSCS.

[0036] (4) Preparation of multifunctional composite injectable hydrogel (HC@PTM) The OHA solution with a mass concentration of 5 wt% containing PTM micelles and the HA-ADH with a mass concentration of 6 wt% containing NSCS and ADH were fully mixed in equal volumes to obtain HC or HC@PTM.

[0037] Example 2 In this example, based on Example 1, 5 wt% OHA solution containing and not containing PTM micelles and 6 wt% NSCS and HA-ADH containing ADH were mixed in equal volumes to obtain HC or HC@PTM. The following experimental studies were carried out on the performance of PTM, HC, and HC@PTM in Example 1.

[0038] Experiment 1: The PTM in Example 1 was used to evaluate the particle size and morphology of the micelles using scanning electron microscopy (SEM) and dynamic light scattering spectrometer (DLS). Figure 4-5 shown.

[0039] By the attached Figure 4-5 The data show that the hydrodynamic diameter of MTX is about 250 nm, and the scanning electron microscope image shows that PTM is spherical, indicating that PTM can self-assemble into nanomicelles.

[0040] The size changes of micelles in solutions containing 100mM H2O2 and without H2O2 were measured to detect the sensitivity of micelles to reactive oxygen species. Under normal conditions (without H2O2), the DLS curve of PTM showed a relatively uniform single-peak distribution, indicating that the particle size distribution of micelles was relatively uniform; while in solutions containing H2O2, the DLS curve of PTM showed multiple peaks and the size distribution was extremely uneven, indicating that in the ROS environment, ketalthiols can be oxidatively cleaved, resulting in the dissociation of PTM self-assembled polymer micelles, thereby releasing the drug MTX.

[0041] Experiment 2: The following experimental study was carried out on the composite hydrogel prepared in Example 1. The concentration of HA-CHO remained unchanged at 50 mg / mL to obtain solution component A, and NSCS and ADH were mixed at equal concentrations and volumes to obtain sol component B. When the concentration of sol component B was 50 mg / mL, 60 mg / mL, and 70 mg / mL and mixed with solution component A, gels were obtained, recorded as HC-1, HC-2, and HC-3, respectively. In addition, a composite hydrogel loaded with 5 mg / mL polymer micelles was also prepared, recorded as HC@PTM.

[0042] (1) To investigate the network stability of these gels, an oscillatory frequency sweep method was used while maintaining a constant strain amplitude of 1%. This method was used to evaluate the mechanical properties and stability of the samples by measuring their storage modulus (G') and loss modulus (G"). The results are shown in the Appendix. Figure 6 As shown. Figure 6The data show that within the angular frequency range of 1 to 100 rad / s, the storage modulus (G') of all samples is always greater than their loss modulus (G"), indicating that elastic deformation dominates with increasing angular frequency. Network stability: The storage modulus (G') is greater than the loss modulus (G"), which is an important sign of the stability of the gel network structure. This indicates that the gel can exhibit more elastic behavior rather than viscous behavior when subjected to external force. Therefore, these gels have a stable network structure. Effect of angular frequency: As the angular frequency increases, elastic deformation dominates, which further confirms the stability of the gel network structure. The increase in angular frequency means that the frequency of external force increases, but the gel is still able to maintain its structural integrity and does not exhibit excessive viscous flow. Effect of concentration: Since gels of all concentrations exhibit similar behavior (i.e., G'>G"), they all have relatively stable network structures.

[0043] In summary, the experimental results show that the composite hydrogels (HC-1, HC-2, HC-3 and HC@PTM) prepared by the method of the present invention exhibit a stable network structure under oscillation frequency scanning, and these gels can exhibit more elastic behavior rather than viscous behavior when subjected to external forces, which provides strong support for their stability and performance in practical applications.

[0044] (2) Schiff base-based hydrogels exhibit good mechanical properties, making in situ injection, self-healing, and integration into minimally invasive and precision medicine possible. The results are shown in the attached Figure 7 shown.

[0045] By the attached Figure 7 The data show that with the increase of shear rate, the viscosity of HC and HC@PTM gradually decreases, showing shear thinning behavior, which is a common phenomenon when fluids are subjected to shear force, making the fluids easier to inject or extrude; at the same shear rate, the viscosity of HC@PTM is lower than that of HC, which means that HC@PTM has better fluidity and injectability; continuous injection of HC@PTM into PBS solution maintains the gel state without affecting the structure, highlighting its superior writing ability, such as being injected into a flower shape, further demonstrating its good injectability and shape retention ability.

[0046] like Figure 8 As shown, to simulate the filling of hydrogels in different molds, the hydrogels were injected into a bottle with a cardboard shell to fill its pores completely by gravity. At the same time, without external intervention, the HC@PTM hydrogel can actively adapt to the shape of the mold, indicating that its potential shape adaptability can match the irregular cartilage.

[0047] (3) Self-healing ability assessment In order to evaluate the self-healing ability of the hydrogel, a step-by-step strain scanning method was used. By applying different strain conditions to the hydrogel at different time periods, the changes in its mechanical properties were observed. The hydrogel was first scanned under high strain conditions to observe the dissociation and collapse of its network structure. Then, the strain was restored to a lower level of 1%, and the recovery of the hydrogel over a period of time was observed. The results are shown in the attached figure. Fig. 9 shown.

[0048] By the attached Fig. 9 The data show that under high strain conditions, both the storage modulus (G') and loss modulus (G") of the hydrogel changed significantly, indicating that its network structure dissociated and collapsed. This is because under high strain, the cross-linking points inside the hydrogel may be damaged, causing the network structure to become unstable; when the strain is restored to a lower level of 1%, the HC@PTM hydrogel shows the ability to almost completely restore G' to its original state within 100 seconds. This shows that the HC@PTM hydrogel has excellent recovery and self-healing ability. Even after two strain-induced failure cycles, HC@PTM is still able to show microstructural reconstruction, further demonstrating its excellent mechanical properties; through macroscopic observation, the experiment found that two hydrogel slices were able to fuse into one piece after 1 hour of contact. This shows that the HC@PTM hydrogel undergoes chemical bonding or physical cross-linking at the contact interface, thereby achieving self-healing. The healed hydrogel maintains its integrity under gravity and can be manipulated with tweezers, further demonstrating the reliability of its self-healing ability.

[0049] In summary, the experimental results show that HC@PTM hydrogel has a certain self-healing ability and can withstand large deformations at the joints. This self-healing ability makes HC@PTM hydrogel have broad prospects in biomedical applications, especially in tissue engineering that needs to withstand complex deformation and stress environments.

[0050] (4) Swelling and degradation of gel The swelling and degradation of the gel is an important property that can directly affect the drug loading and drug release performance of the hydrogel. The HC@PTM hydrogel prepared in Example 1 has environmentally dependent swelling and degradation properties, which can provide a good basis for the intelligent release of drugs. The swelling and degradation profile of the composite hydrogel at pH = 7.4 is shown in the attached Fig.10 As shown in the figure; the swelling and dissolution spectrum at pH = 6.8, the results are shown in the attached Fig.11 shown.

[0051] By the attached Figure 10-11The data show that the swelling characteristics analysis: within the time range of 0 to 24 hours, all gels showed a certain increase in water absorption; the water absorption curve of HC@PTM rose rapidly in the early stage and then stabilized, indicating that it has good swelling properties and can quickly absorb water to reach saturation; in contrast, the water absorption curves of HC-1 and HC-2 rose slowly, and the saturated water absorption rate finally reached was also lower than that of HC@PTM, indicating that their swelling properties under the same conditions were not as good as HC@PTM. Degradation characteristics analysis: within the time range of 0 to 42 days, all gels showed a certain increase in degradation rate; the degradation rate curve of HC@PTM grew slowly in the early stage and then gradually accelerated, but the overall degradation rate was relatively controllable, indicating that it has good degradation stability; the degradation rate curves of HC-1 and HC-2 showed a faster growth trend, especially in the later stage of the experiment, the degradation rate was significantly accelerated, which may mean that they may face faster degradation and performance degradation in long-term applications. It can be seen that it exhibits pH-responsive behavior, which is conducive to the long-term stable intelligent release of micelle PTM and drug MTX. The HC@PTM hydrogel prepared in Example 1 exhibits excellent environment-dependent swelling and degradation properties under a pH=7.4 environment. It has good swelling properties and can quickly absorb water to reach a saturated state; at the same time, its degradation rate is relatively controllable and has good degradation stability. These properties provide a good basis for the intelligent release of drugs, making HC@PTM hydrogel have potential application value in the fields of drug carriers and intelligent release systems.

[0052] Experiment 3: Controlled drug release of composite hydrogels In order to explore the long-term controlled release ability of the HC@PTM composite hydrogel prepared in Example 1, 1 mL of the HC@PTM hydrogel and PTM prepared in Example 1 were added, and the supernatant was aspirated at a fixed time to detect the MTX content therein. The sustained release curve of the hydrogel is shown in FIG. Fig.12 shown.

[0053] By the attached Fig.12The data show that the MTX release rate comparison: MTX encapsulated in PTM is almost completely released within 12 hours. In contrast, the MTX release rate of HC@PTM in 12 hours is only 32.51% (pH=7.4), showing a slower release characteristic, which indicates that HC@PTM composite hydrogel can more effectively control the release rate of the drug; long-term controlled release ability: the cumulative release rate of HC@PTM composite hydrogel on the 10th day is about 60.12%, which indicates that it has good long-term controlled release ability. The drug can be continuously released for a long time, which may provide a more lasting therapeutic effect; pH-responsive carrier properties: HC@PTM hydrogel shows accelerated release at pH=6.8, which further confirms its pH-responsive carrier properties, meaning that HC@PTM composite hydrogel can adjust the release rate of the drug according to different pH environments, thereby providing more precise treatment under different physiological conditions; therapeutic application potential: compared with the use of PTM alone, HC@PTM composite hydrogel as a PTM smart drug library can prolong and control the release of drugs. This shows the potential for long-term superior efficacy in the treatment of RA (and possibly rheumatoid arthritis). By precisely controlling the release rate and duration of the drug, the HC@PTM composite hydrogel may be able to more effectively alleviate symptoms, reduce side effects, and improve the quality of life of patients.

[0054] In summary, this experiment revealed the advantages of HC@PTM composite hydrogel in drug controlled release by comparing the release of MTX in a fixed time with that of PTM. Its slower release characteristics, good long-term controlled release ability and pH-responsive carrier properties make HC@PTM composite hydrogel have broad application prospects in the treatment of RA.

[0055] Experiment 4: Active oxygen scavenging ability of composite hydrogel In order to demonstrate the ROS scavenging ability of the composite hydrogel, the antioxidant effect of PTM, HC and HC@PTMBP@PDA on 1,1-diphenyl-2-methylsalicylic acid free radical (DPPH) was used to characterize the ROS scavenging activity. DPPH is a stable RNS compound, and its ethanol solution is dark purple with a characteristic absorption peak at 517nm. The scavenging of DPPH by HC@PTM hydrogel was tested, and the results are shown in the attached Fig.13 shown.

[0056] By the attached Fig.13It can be seen that with the increase of DPPH concentration, the position of the absorption peak moves to the right (i.e., the wavelength increases), and the absorption intensity increases, which indicates that there is a positive correlation between the concentration of DPPH solution and the absorbance; by comparing the DPPH scavenging rates of HC, PTM and HC@PTM, it can be clearly seen that the addition of PTM significantly improves the antioxidant properties of the composite hydrogel; the high scavenging rate of HC@PTM indicates that it has good ROS scavenging ability and is expected to become a candidate material for improving the oxidative stress microenvironment in the treatment of RA (rheumatoid arthritis).

[0057] Experiment 5: Determination of the anti-inflammatory ability of composite hydrogels in vitro Fluorescent probe DCFH-DA was used to detect the level of intracellular reactive oxygen species and evaluate its ability to scavenge reactive oxygen species. In the hydrogen peroxide-induced oxidative stress model, blank culture medium was used as a control, and ADTC5 cells were cultured on HC, PTM, and HC@PTM, respectively. Flow cytometry was used to detect the level of reactive oxygen species in vitro. The results are shown in the attached Fig.14 shown.

[0058] By the attached Fig.14 The data show that the level of intracellular ROS in different experimental groups was detected by flow cytometry, and the results showed that HC@PTM hydrogel has significant ROS scavenging ability. Compared with HC and PTM, HC@PTM showed a stronger ROS scavenging effect, which is beneficial to the clearance of inflammation in bone and joints. This discovery provides new possibilities and directions for the application of HC@PTM in the treatment of bone and joint diseases.

[0059] Experiment 6: Composite hydrogel for the treatment of rheumatoid arthritis in mice To evaluate the effect of in vivo treatment, RA models were randomly divided into 4 groups in mice: model group, HC, PTM and HC@PTM. The schedule of animal experiments and the results are shown in the Appendix. Fig.15 shown.

[0060] The morphological characteristics of each group were compared by HE, toluidine blue, safranin O-fast green and type II collagen staining to evaluate the in vivo efficacy of different methods in the treatment of rheumatoid arthritis. The results are shown in the attached Fig.16 shown.

[0061] By the attached Fig.16The results showed that compared with the HC group, RA inflammation in the PTM group and HC@PTM group was significantly improved, as manifested by reduced synovial hyperplasia and reduced inflammatory cell infiltration; the aminoglycan-positive area in the PTM group and HC@PTM group increased, indicating that the protection and repair of cartilage tissue were enhanced; the number of mature chondrocytes also increased in the PTM group and HC@PTM group, further confirming the protective and regenerative effects of these two treatments on cartilage; the HC@PTM group showed the most effective cartilage repair treatment results in RA mice, which was due to the synergistic effect of HC and PTM, which significantly improved the treatment effect.

[0062] In summary, the HC@PTM group showed the best effect in the treatment of RA, which could significantly improve joint inflammation and promote the repair and regeneration of cartilage, providing important experimental basis and reference for further research and development of new treatment methods for RA.

[0063] The above contents are merely examples and explanations of the concept of the present invention. Various modifications or supplements made to the described specific embodiments or replacements made by technicians in the technical field in this field in a similar manner shall fall within the protection scope of the present invention as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims.

Claims

1. A method for preparing a multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles, characterized in that: include: S1, sodium periodate aqueous solution reacts with hyaluronic acid at room temperature, dialyzes, and dries to obtain dialdehyde hyaluronic acid; S2, chitosan is dissolved, the solution containing succinic anhydride reacts, the precipitate is collected and dialyzed, and freeze-dried to obtain succinic anhydride-modified chitosan; S3, preparation of active oxygen responsive polymer micelles; S4, dialdehyded hyaluronic acid is dissolved in a solution containing polymer micelles, and mixed with chitosan modified with succinic acid and adipic acid dihydrazide solution to obtain a multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles; The mass concentration of the dialdehyde hyaluronic acid solution is 3%~7%; the mass concentration of succinic acid modified chitosan is 5wt%~7wt%, the mass concentration of adipic acid dihydrazide solution is 5wt%~7wt%; the concentration of active oxygen responsive polymer micelles.

2. The method for preparing the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles according to claim 1, characterized in that: In S1, the molar ratio of sodium periodate to hyaluronic acid is 1-2:

1.

3. The method for preparing the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradable polymer micelles according to claim 1, characterized in that: In S2, the molar ratio of chitosan to succinic anhydride is 1:1-3, and the reaction is carried out at 23°C-27°C for 11 h-15 h.

4. The method for preparing the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles according to claim 1, characterized in that: In S3, the step of preparing active oxygen responsive polymer micelles comprises: S31, mixing 3-mercaptopropionic acid, acetone and trifluoroacetic acid, stirring at room temperature, ice bathing until crystallization is complete, filtering, washing, and drying to obtain ketal mercaptan; S32, stirring thioketal, N,N'-diisopropylcarbodiimide and 4-dimethylaminopyridine in dichloromethane, adding dropwise methoxy polyethylene glycol 2000 dissolved in dichloromethane, stirring under nitrogen atmosphere, precipitating with cold ether three times, filtering, dissolving the solid in water, and dialyzing to obtain methoxy polyethylene glycol-thioketal; S33, adding methoxy polyethylene glycol-ketalthioate to a dimethylsulfoxide aqueous solution containing N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, stirring at room temperature, adding ammonia disodium solution dropwise, stirring for reaction, dialyzing, and freeze-drying to obtain methoxy polyethylene glycol-ketalthioate-methyldisodium; S34, dissolving methoxy polyethylene glycol-thioketal-methylamine dispersant, ultrasonicating in a water bath, and assembling in water to obtain active oxygen responsive polymer micelles; the methoxy polyethylene glycol-thioketal-methylamine dispersant is dissolved in dimethyl sulfoxide at a concentration of 1 mg / mL~5 mg / mL, and the volume ratio of dimethyl sulfoxide to water is 1~2:

1.

5. The method for preparing the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradable polymer micelles as claimed in claim 4, characterized in that: In S31, the mass ratio of the 3-mercaptopropionic acid, acetone and trifluoroacetic acid is 5-6:2-3:

1.

6. The method for preparing the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradable polymer micelles as claimed in claim 4, characterized in that: In S32, the mass ratio of thioketal, N,N'-diisopropylcarbodiimide and 4-dimethylaminopyridine is 1~2:1:0.1~0.

2.

7. The method for preparing the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradable polymer micelles as claimed in claim 4, characterized in that: In S33, the feed mass ratio of the methoxy polyethylene glycol-thioketal, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is: 6~7:0.6~0.7:0.7~0.

9.

8. The method for preparing the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradable polymer micelles as claimed in claim 1, characterized in that: In S4, the volume ratio of the dialdehyde hyaluronic acid solution to the adipic acid dihydrazide solution of succinic acid-modified chitosan is 1:

1.

9. A multifunctional injectable composite hydrogel loaded with active oxygen responsive degradation polymer micelles obtained according to the preparation method according to any one of claims 1 to 8.

10. Use of the multifunctional injectable composite hydrogel loaded with active oxygen responsive degradable polymer micelles according to claim 9 in the preparation of an injectable medicament for rheumatoid arthritis.